2019
DOI: 10.1093/jamia/ocz178
|View full text |Cite
|
Sign up to set email alerts
|

Training medical students and residents in the use of electronic health records: a systematic review of the literature

Abstract: Objective Our objectives were to identify educational interventions designed to equip medical students or residents with knowledge or skills related to various uses of electronic health records (EHRs), summarize and synthesize the results of formal evaluations of these initiatives, and compare the aims of these initiatives with the prescribed EHR-specific competencies for undergraduate and postgraduate medical education. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Such an analysis should explore the content, duration, pedagogy, learning objectives, course integration, assessment methods, format, delivery, and evaluation of reported digital health courses with the aim of informing the development of future courses. Several reviews have been published focusing on training in specific areas within digital health, such as telemedicine [24][25][26], electronic health record (EHR) training [27], computer literacy, and medical informatics [28,29]. However, digital health education should be comprehensive and systematic [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Such an analysis should explore the content, duration, pedagogy, learning objectives, course integration, assessment methods, format, delivery, and evaluation of reported digital health courses with the aim of informing the development of future courses. Several reviews have been published focusing on training in specific areas within digital health, such as telemedicine [24][25][26], electronic health record (EHR) training [27], computer literacy, and medical informatics [28,29]. However, digital health education should be comprehensive and systematic [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…21 Curricula in EHRs have been piloted in medical education, although none specifically in the field of ophthalmology, and of the 11 reported interventions, only 4 target residents. 22 Educational strategies that have been described previously in EHR curricula include simulated EHRs with virtual patients and scribes, review and correction of sample charts, web-based modules, and direct faculty observation with reflective assessment. 21,23e28 Trainees should also be able to use the EHR to communicate effectively with other providers by clearly demonstrating the thought process in problem-based organized notes with supporting data incorporated into each subheading.…”
Section: Electronic Health Record Educationmentioning
confidence: 99%
“…In turn, the authors of the program considered as one of the main difficulties a necessity of database updating with regard to decease treatment recommendations and guidelines. A positive effect of using EMR in training of higher medical schools' students was demonstrated in [10][11][12] as an important part of an education, while students, in turn, reported that mastering EMR had a positive role in preparing them for a future profession [13,14].…”
Section: Related Workmentioning
confidence: 99%